Broadband Spintronic Terahertz Source with Peak Electric Fields Exceeding 1.5 MV/cm - Rouzegar, R.; Chekhov, A. L.; Behovits, Y.; Serrano, B. R.; Syskaki, M. A.; Lambert, C. H.; Engel, D.; Martens, U.; Münzenberg, M.; Wolf, M.; Jakob, G.; Kläui, M.; et al. (Physical Review Applied, 2023)
In this work, we improve the performance of an optically pumped spintronic terahertz emitter (STE) by a factor of up to 6 in field amplitude through an optimized photonic and thermal environment. Using high-energy pump pulses (energy 5 mJ, fluence >1 mJ/cm2, wavelength 800 nm, duration 80 fs), we routinely generate terahertz pulses with focal peak electric fields above 1.5 MV/cm, fluences of the order of 1 mJ/cm2, and a spectrum covering the range 0.1-11 THz. Remarkably, the field and fluence values are comparable to those obtained from a state-of-the-art terahertz table-top high-field source based on tilted-pulse-front optical rectification in LiNbO3. The optimized STE inherits all attractive features of the standard STE design, for example, ease of use and the straightforward rotation of the terahertz polarization plane, without the typical 75% power loss found in LiNbO3 setups. It, thus, opens up a promising pathway to nonlinear terahertz spectroscopy. Using low-energy laser pulses (2 nJ, 0.2 mJ/cm2, 800 nm, 10 fs), the emitted terahertz pulse has a focal peak electric field of 100 V/cm, which corresponds to a 2-fold improvement, and covers the spectrum 0.3-30 THz.
CRIS-Team Scopus Importer:2023-03-27